Ethanol Extracts of Solanum lyratum Thunb Regulate Ovarian Cancer Cell Proliferation, Apoptosis, and Epithelial-to-Mesenchymal Transition (EMT) via the ROS-Mediated p53 Pathway - Chen Zhang; Zheming Li; Jie Wang; Xuelu Jiang; Mengting Xia; Jianfen Wang; Shenyi Lu; Shouye Li; Hanmei Wang (Journal of Immunology Research)
Ovarian cancer is a type of common gynecological tumors with high incidence and poor survival. The anticancer effects of the traditional Chinese medicine Solanum lyratum Thunb (SLT) have been intensively investigated in various cancers but in ovarian cancer is rare. The current study is aimed at investigating the effect of SLT on ovarian cancer cells. Lactate dehydrogenase (LDH) and MTT assays indicated that SLT concentrations of 0.25 and 0.5 μg/mL were not cytotoxic and had significant inhibitory effects on the cell viabilities of A2780 and SKOV3 cells, hence were used for subsequent experiments. Flow cytometric and western blot analysis revealed that SLT effectively suppressed ovarian cancer cell proliferation via inducing cell cycle arrest and increasing apoptosis. Cell cycle and apoptosis-related protein expressions were also regulated in SLT-treated cells. Moreover, DCFH-DA and western blot assays demonstrated that SLT enhanced ROS accumulation and subsequently activated the p53 signaling pathway. However, SLT-regulated ovarian cancer cell proliferation, apoptosis, migration, invasion, and EMT were significantly reversed by an ROS inhibitor (NAC, N-acetyl-L-cysteine). Furthermore, A2780 and SKOV3 cells cocultured with M0 macrophages showed that SLT activated the polarization of M0 macrophages to M1 macrophages and inhibited the polarization to M2 macrophages, with the increased percentage of CD86+ cells and decreased percentage of CD206+ cells were detected. In summary, this study illustrated the anticancer effects of SLT on ovarian cancer cells, suggesting that SLT may have the potential to provide basic evidence for the discovery of antiovarian cancer agents.